Multi-marker phylogeny of three evergreen oaks reveals vicariant patterns in the Western Mediterranean - de Heredia, U L; Jimenez, P; Collada, Carmen (Taxon, 2007)
Nuclear (AFLPs and ITSs) and chloroplast DNA markers (cpDNA) were analysed in Quercus suber L., Q. ilex L. and Q. coccifera L. in order to detect vicariant patterns in the Western Mediterranean Basin populations. Clustering methods, i.e., parsimony, minimum spanning network, UPGMA and PCO, were used to obtain robust phylogenies. The Mantel test was used to check the geographic structure of the populations. Nuclear markers’ based phylogenies showed high bootstrap values at basal nodes of clusters indicative of species. Within species, Q. suber and Q. ilex showed three and two groups respectively with strong geographic structure for cytoplasmic and nuclear markers. In contrast, Q. coccifera had overlapping cpDNA lineages and nuclear markers did not show any group with strong geographic structure. Taxonomic assignation of the species was well-supported by our data. Ongoing allopatric speciation was inferred for Q. suber and Q. ilex derived from Pliocene vicariant events. Quercus coccifera showed a more homogeneous genetic pattern in the Western Mediterranean.
Keywords: AFLP; cpDNA; ITS; mediterranean quercus; phylogeny; vicariance

Análisis de la variabilidad de adn de cloroplastos en Quercus ilex L., Q. suber L. Y Q. coccifera L.. - COLLADA, C; Jimenez, P; Gil, L (III Congreso Forestal Español, 2001)
Chloroplast (Cp) and mitochondrial (mt) DNA variation have been studied by PCR-RFLP in 14 location (13 with Q. suber, 12 with Q. ilex and 6 with Q. coccifera) along the natural distribution area of these species in the Iberian Peninsula. Five chloroplast DNA primers pairs and one mitochondrial DNA primer pair have been used, each one in combination with a restriction enzyme. 29 different haplotypes have been detected, In the case of Q. suber a characteristic haplotype, very divergent of the remaining ones has been described. Usually, species don’t share haplotypes within the same populations. The distribution of haplotypes suggests a geographical structuring. The levels of genetic differentiation are similar to those obtained in oaks.hS is significantly higher in Q. ilex (hS=0,262). Differentiation coefficients (Gst) are similar in the three species and indicate a high typical structuring of maternal markers.
Keywords: chloroplast DNA; differentiation; geographic distribution; Haplotypes; phylogeny; Quercus

Genetic variation in central and marginal populations of Quercus suber L. - Jimenez, P; Agundez, D; Alia, R; Gil, L (SILVAE GENETICA, 1999)
Eighteen spontaneous populations of cork oak (Quercus suber) from Spain (14), Portugal (1), Morocco (1) and Italy (2), were surveyed at 14 loci from 12 enzyme systems. Percentage of polymorphic loci (64%), mean number of alleles (2.07), and mean expected heterozygosity (0.158) values were within the ranges described for the genus. Populations from the central range of the species and from peripheral areas were evaluated, and differences between these two kinds were assessed. Significant lower diversity (number of alleles and expected heterozygosity) was found for the most isolated and small size populations in contrast to central forests, showing the existence of mechanisms maintaining the levels of diversity even in some ;isolated stands. Interpopulation diversity (F-st) is 3.3%, indicating extensive gene flows or recent postglacial expansion. A possible recent bottleneck is detected in two populations by comparing actual with expected heterozygosity from the number of detected alleles.
Keywords: Genetic Variation; isolation; isozymes; marginal populations.; Quercus suber